Assessment of Physicochemical and Bacteriological Quality of Government Intervention Borehole Water in Ipetu-Ijesa, Osun State (Lafia Journal of Scientific and Industrial Research, 2025)
Access to clean and safe drinking water remains a significant public health concern in Nigeria, where millions lack improved water sources. This study assessed the physicochemical and bacteriological quality of water from selected government intervention boreholes in Ipetu-Ijesa, Osun State. Water samples were collected from five boreholes and analysed for parameters including pH, electrical conductivity, turbidity, total dissolved solids (TDS), dissolved oxygen (DO), nitrate levels, salinity, and microbial contamination (total coliform and Escherichia coli counts). The results indicated that most physicochemical parameters fell within the permissible limits set by the World Health Organisation (WHO) and Nigerian Standards for Drinking Water Quality (NSDWQ). However, turbidity and total coliform counts exceeded safe limits in some locations. Total coliform counts ranged from 2.0 to 14.0 cfu/100 mL with a mean value of 7.0 cfu/100 mL. Borehole D (Oko Owo) exhibited the lowest contamination levels, while Borehole C (Bamikemo) recorded the highest total coliform count. No faecal coliforms were detected in the examined samples. Boreholes A, B, and C exhibited elevated conductivity, TDS, and temperature, suggesting potential contamination from environmental and anthropogenic sources. Borehole D had slightly acidic water, indicating possible metal leaching. Principal Component Analysis (PCA) revealed strong correlations between conductivity, TDS, and temperature, highlighting potential underground contamination sources. Although the physicochemical characteristics and total coliform counts were mostly within permissible limits, deviations in some boreholes suggest the need for continuous monitoring and quality assessment to ensure safe drinking water.
Keywords: Coliform; physicochemical; boreholes; water quality; bacteria